A medical waste sorter for treating on car - LIU YAN; LI GUANGZHEN; GU YINGJIANG; XU HOUPING; WANG YIPING; LI SULIAN; TAN YAN; ZHANG MINGWEI (2018)
The utility model discloses a medical waste sorter for treating on car, including base (1), collecting vessel (2), collecting vessel (2) including ladle body (21) and with bung (22) of ladle body (21)opening looks adaptation, collecting vessel (2) have two at least, the upper surface of base (1) is equipped with two at least concave surfaces, collecting vessel (2) are arranged in in the concave surface, the concave surface with the lower part looks adaptation of collecting vessel (2), the lower bottom surface and the lower stratification object plane of treatment car of base (1) are laminatedmutually. The utility model provides a medical waste sorter for treating on car can classify to medical waste to avoid medical waste to leak effectively. 本实用新型公开种用于治疗车上的医疗废物分类装置，包括底座(1)，收集桶(2)；所述收集桶(2)包括桶身(21)和与所述桶身(21)开口相适配的桶盖(22)；所述收集桶(2)至少有两个；所述底座(1)的上表面设有至少两个凹面；所述收集桶(2)置于所述凹面中；所述凹面与所述收集桶(2)的下部相适配；所述底座(1)的下底面与治疗车的下层置物面相贴合。本实用新型提供的用于治疗车上的医疗废物分类装置，能够对医疗废物进行分类，并有效地避免医疗废物外泄。